Selective sympathetic action on heart rate variability after ultrasound-guided stellate ganglion block - Keim, Ole C.; Raum, Raoul C.; Feldmann, Robert E.; Kleinböhl, Dieter; Benrath, Justus (Autonomic neuroscience, 2026)
Objective - Stellate ganglion block (SGB) blocks the sympathetic branch of the autonomous nervous system, but its specific effects on heart rate variability (HRV) remain widely unidentified in detail. Additionally, under anatomically perspective the vagus nerve is adjacent located to the stellate ganglion. Therefore, the vagus nerve may be affected by a SGB as well. This study aimed at assessing the possibility of selectively blocking efferent sympathetic fibers to the heart and upper extremity via an ultrasound-guided SGB technique. - Methods - In a placebo-controlled, double-blind trial based on a within-subject design, twelve healthy male volunteers received a right-sided ultrasound-guided SGB (usSGB) with 3 ml ropivacaine 1 % (verum) or saline 0.9 % solution (placebo), respectively. HRV was assessed during a pre- and post-intervention section. - Results - No significant changes were detected in time domain-based HRV indices before and after the usSGB between verum and placebo. However, significant differences between both were found in the low frequency/high frequency ratio (LF/HF ratio) before and after the procedure. - Conclusion - The current study demonstrates that usSGB renders HRV changes indicating selective sympathetic inhibition of the heart without affecting vagal tone.